2004
DOI: 10.1889/1.1825717
|View full text |Cite
|
Sign up to set email alerts
|

36.3: Invited Paper: Color Phosphors for Inorganic Electroluminescent Devices

Abstract: Significant progress in the performance and commercialization of full‐color thin‐film electroluminescent (EL) displays has been achieved. This is due to the remarkable progress made in the performance of existing EL phosphors, development of new phosphor materials, and design of new EL phosphor structures. In this paper, I describe the progress in the development of EL phosphor materials based on systematical study of Eu and Mn ion doped ternary compounds. Highly saturated phosphor that realizes full color dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…CaAl 2 S 4 :Eu,Gd was reported as an efficient green TFEL phosphor, with a luminance of 3000 cd/m² at 1 kHz and was prepared with a dual source e-beam technique [ 131 ]. With this phosphor, a wider color gamut can be obtained in comparison to SrGa 2 S 4 :Eu [ 132 ].…”
Section: Thin Film Electroluminescencementioning
confidence: 99%
“…CaAl 2 S 4 :Eu,Gd was reported as an efficient green TFEL phosphor, with a luminance of 3000 cd/m² at 1 kHz and was prepared with a dual source e-beam technique [ 131 ]. With this phosphor, a wider color gamut can be obtained in comparison to SrGa 2 S 4 :Eu [ 132 ].…”
Section: Thin Film Electroluminescencementioning
confidence: 99%
“…The emission of an as-deposited sample slightly shifted to a longer wavelength region compared with that of the device annealed at 800 C, although the blue EL with a peak at 475 nm was observed at a substrate temperature of 650 C during the deposition. 8,9) Tanaka and Okamoto also obtained the BaAl 2 S 4 :Eu phosphor films without an annealing process by a molecular-beam epitaxy (MBE) system. 10) Under the phosphor preparation conditions with the MBE method, substrate temperature is still high, and it was reported that a flux agent is necessary to improve the crystallinity of thinfilm phosphors.…”
Section: Introductionmentioning
confidence: 99%